BREAKING MODEL OF SINTERED STEELS - Cristina IONICI (Fiabilitate şi Durabilitate, 2013)
The structure of sintered steel pores and their distribution is described in terms of breaking model. Thefound correspondence between pore distribution and crack is examined. The most important theoretical problemis to find the correspondence between macro- and meso-scopic picture of fatigue